Repast Based on a Novel by Fumiko Hayashi - Naruse, Mikio; Tamai, Masao; Uehara, Ken; Hara, Setsuko; Shimazaki, Yukiko (Eureka Video, 2006)
"Repast" is a family drama set in Osaka and Tokyo shortly after the end of World War II. Economic circumstances make life difficult for Michiyo, an Osaka housewife played by Ozu regular Setsuko Hara in an exceptionally nuanced performance. She has been married for five years and the dream of a better life has faded. Her husband Hatsunosuke (Ken Uehara) has a low paying job and her life consists only of the repetitive chores of cleaning, washing, and cooking with no promise of a better future, a fact that she draws constant attention to. Michiyo is at first welcoming when Hatsunosuke's niece Satoko (Yukiko Shimazaki) comes to visit but soon becomes annoyed and jealous when her husband takes her on a tour of Osaka and pays an inordinate amount of attention to her charms. When her dissatisfaction becomes crystallized, she decides to return to Tokyo to visit her mother. She is torn between wanting to find a job and remaining separated or returning to her husband to continue with the struggle ... [www.talkingpix.co.uk]
Keywords: DVD-Video